Mapping the landscape and exploring trends in macrophage-related research within non-small cell lung cancer: a comprehensive bibliometric analysis - Zhou, Yinxue; Wu, Tingyu; Sun, Jiangxing; Bi, Huanhuan; Xiao, Yuting; Wang, Hongmei (Frontiers in Immunology, 2024)
Background：Macrophages play a pivotal role in the research landscape of non-small cell lung cancer (NSCLC), contributing significantly to understanding tumor progression, treatment resistance, and immunotherapy efficacy. In this study, we utilized bibliometric techniques to analyze shifts in research hotspots and trends within the field, while also forecasting future research directions. These insights aim to offer guidance for both clinical therapeutic interventions and foundational scientific inquiries. Methods: All publications were released between 1993 and 2023 and focus on research pertaining to macrophages in the field of NSCLC. The articles were identified from the Web of Science Core Collection and analyzed using VOSviewer 1.6.19, CiteSpace 6.2.R2, and Scimago Graphica 1.0.35. Result: A total of 361 articles authored by 3,072 researchers from 48 countries were included in the analysis. TAMs have gained increasing attention for their role in NSCLC development and as potential therapeutic targets. Modulating TAM behavior may offer avenues to suppress tumor growth and drug resistance, improving patient outcomes. International collaboration, particularly between China and the United States, accelerates progress in NSCLC research, benefiting patients worldwide. The research hotspot revolves around understanding the role of macrophages in immunotherapy, focusing on their contribution to tumor progression, therapeutic resistance, and potential as therapeutic targets in NSCLC.The therapeutic significance of macrophages in the field of NSCLC is gaining increasing attention and recognition, highlighting their potential as key players in the development of novel treatment strategies. Future research will focus on understanding TAM molecular mechanisms, interactions with immune cells, and exploring novel therapies, with the aim of improving NSCLC treatment outcomes.